Individualized positive end-expiratory pressure titration strategies in superobese patients undergoing laparoscopic surgery: prospective and nonrandomized crossover study - Bösing, Christoph; Schäfer, Laura Sophie; Hammel, Marvin; Otto, Mirko; Blank, Susanne; Pelosi, Paolo; Rocco, Patricia R. M.; Lücke, Thomas; Krebs, Jörg (Anesthesiology, 2023)
Superobesity and laparoscopic surgery promote negative end-expiratory transpulmonary pressure that causes atelectasis formation and impaired respiratory mechanics. The authors hypothesized that end-expiratory transpulmonary pressure differs between fixed and individualized positive end-expiratory pressure (PEEP) strategies and mediates their effects on respiratory mechanics, end-expiratory lung volume, gas exchange, and hemodynamic parameters in superobese patients.In this prospective, nonrandomized crossover study including 40 superobese patients (body mass index 57.3 ± 6.4 kg/m2) undergoing laparoscopic bariatric surgery, PEEP was set according to (1) a fixed level of 8 cm H2O (PEEPEmpirical), (2) the highest respiratory system compliance (PEEPCompliance), or (3) an end-expiratory transpulmonary pressure targeting 0 cm H2O (PEEPTranspul) at different surgical positioning. The primary endpoint was end-expiratory transpulmonary pressure at different surgical positioning; secondary endpoints were respiratory mechanics, end-expiratory lung volume, gas exchange, and hemodynamic parameters.Individualized PEEPCompliance compared to fixed PEEPEmpirical resulted in higher PEEP (supine, 17.2 ± 2.4 vs. 8.0 ± 0.0 cm H2O; supine with pneumoperitoneum, 21.5 ± 2.5 vs. 8.0 ± 0.0 cm H2O; and beach chair with pneumoperitoneum; 15.8 ± 2.5 vs. 8.0 ± 0.0 cm H2O; P < 0.001 each) and less negative end-expiratory transpulmonary pressure (supine, −2.9 ± 2.0 vs. −10.6 ± 2.6 cm H2O; supine with pneumoperitoneum, −2.9 ± 2.0 vs. −14.1 ± 3.7 cm H2O; and beach chair with pneumoperitoneum, −2.8 ± 2.2 vs. −9.2 ± 3.7 cm H2O; P < 0.001 each). Titrated PEEP, end-expiratory transpulmonary pressure, and lung volume were lower with PEEPCompliance compared to PEEPTranspul (P < 0.001 each). Respiratory system and transpulmonary driving pressure and mechanical power normalized to respiratory system compliance were reduced using PEEPCompliance compared to PEEPTranspul.In superobese patients undergoing laparoscopic surgery, individualized PEEPCompliance may provide a feasible compromise regarding end-expiratory transpulmonary pressures compared to PEEPEmpirical and PEEPTranspul, because PEEPCompliance with slightly negative end-expiratory transpulmonary pressures improved respiratory mechanics, lung volumes, and oxygenation while preserving cardiac output.A number of studies have evaluated the use of varying strategies for determining optimal levels of positive end-expiratory pressure (PEEP) in patients undergoing bariatric or other laparoscopic surgical procedures aimed at optimizing respiratory mechanics that may potentially improve postoperative outcomesConsiderably fewer data are available in “superobese” patients (body mass index 50 kg/m2 or higher)This prospective, nonrandomized, crossover study compared the effects of three PEEP strategies (fixed level 8 cm H20, titration to the highest static compliance, or PEEP targeting a zero end-expiratory transpulmonary pressure) at different surgical positions on end-expiratory transpulmonary pressure (primary outcome) and respiratory mechanics, lung volumes, gas exchange, and hemodynamics (secondary outcomes)Compared to fixed PEEP or zero end-expiratory transpulmonary pressure strategies, titration to the highest static compliance resulted in a slightly negative end-expiratory transpulmonary pressure that was associated with improved respiratory mechanics, lung volumes, oxygenation, and preservation of cardiac output
Online veröffentlicht: 24. Mai 2023
Gesehen am 27.09.2023